Parabolic Foliations on Three-Manifolds - Krouglov, V. (Журнал математичної фізики, аналізу, геометрії, 2009)
We prove that every closed orientable three-manifold admits a parabolicfoliation. Mathematics Subject Classification: 53C12, 57R30.